Are there any strategies to improve neonatal outcomes associated with epidural analgesia in labor? - Armani, Marta; Gaggiano, Carla; Dallaglio, Sara; Romanini, Enzo; Sospiri, Carmen; Magnani, Cinzia (Acta Biomedica Atenei Parmensis, 2013)
Background and aim of the work: This study was aimed at evaluating the relationship between epidural analgesia and perinatal outcomes and at verifying the advisability of procedural changes in assistance to labor.Subjects and methods: From January to December 2012, we conducted a retrospective case-control study on 1,963 laboring pregnant women admitted to the Parma University Hospital. We considered two groups: Group 1 received epidural analgesia and Group 2 received no analgesia. Women with elective cesarean sections, multiple pregnancies or deliveries at